Reconstruction Of Facial Defect In Cancrum Oris - Prof. Masood H. Khan; Dr. Arshad Hafeez Khan; Dr. Mohd. Yaseen; Dr. Farooq Bhat (Indian Journal of Plastic Surgery, 1991)
Reconstruction of composite, massive tissue loss in 12 cases of cancrum oris is carried out. Three different flaps have been used and their merits are listed.